2020
DOI: 10.1016/j.ejim.2020.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bias and accuracy using cystatin C and creatinine in CKD-EPI equations for GFR estimation

Abstract: Background: The directly measured glomerular filtrate rate (mGFR) is the gold standard for kidney function, but it is invasive and costly. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations have been widely used to estimate GFR, however, the comparative accuracy of estimated GFR (eGFR) using creatinine and cystatin C in CKD-EPI equations remains unclear. We performed this meta-analysis to assess the bias and accuracy of eGFR using equations of CKD-EPI crea , CKD-EPI cys , and CKD-EPI cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…In this study, the association between renal function and NF-L is based on cyctatin C. Cystatin C was initially chosen because creatinine is known to be influenced by muscle mass and this cohort was initially designed to evaluate prevalence of sarcopenia. Cystatin C is as good as or even better than creatinine in estimating GFR [ 26 ] although cystatin C is less commonly used on a routine basis because it is more expensive for patients. In previous studies [ 22 , 24 ], renal function was assessed based on creatinine rather than cystatin C emphasizing that our conclusions are driven by renal function rather than by the method that estimates renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the association between renal function and NF-L is based on cyctatin C. Cystatin C was initially chosen because creatinine is known to be influenced by muscle mass and this cohort was initially designed to evaluate prevalence of sarcopenia. Cystatin C is as good as or even better than creatinine in estimating GFR [ 26 ] although cystatin C is less commonly used on a routine basis because it is more expensive for patients. In previous studies [ 22 , 24 ], renal function was assessed based on creatinine rather than cystatin C emphasizing that our conclusions are driven by renal function rather than by the method that estimates renal function.…”
Section: Discussionmentioning
confidence: 99%
“…11,[40][41][42][43][44][45][46] A meta-analysis among populations relevant to primary health care also reported that eGFRcys and eGFRcr-cys were less biased and more accurate than eGFRcr. 49 The heterogenous findings in the performance of eGFRcys could be related to the higher prevalence of smoking or other clinical characteristics in our study population that differ from others. [50][51][52][53] Unlike our decision to develop eGFRcr-PK to account for bias in eGFRcr, presumably because of lower muscle mass and lower dietary protein intakes 19 in Pakistan compared with North American and European populations in which the CKD-EPI eGFRcr was developed, we elected not to develop a calibration factor for eGFRcys in Pakistan because the cause of the large bias of eGFRcys is not known, and therefore we were not confident that the calibrated equation would be robust across the country.…”
Section: Discussionmentioning
confidence: 78%
“…They also indicated that the MDRD equation performed better for females or elderly patients [ 40 ]. In contrast, according to a meta-analyses by Zou et al, CKD-EPI cys was the most accurate compared with CKD-EPI crea/cys , and CKD-EPI crea and performed best in the analyses of sub-group such as those persons with mGFR < 60 mL/min/1.73 m 2 , aged less than 70 years and those participants who were of the Asia ethnic group [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a meta-analysis of 35 studies with 23,667 persons, eGFR measured using CKD-EPI cys had less bias compared with CKD-EPI crea/cys , and CKD-EPI crea . The authors also reported that the projected values from CKD-EPI crea/cys displayed greater accuracy than those from CKD-EPI crea [ 28 ]. Moreover, a systematic and meta-analysis 48 studies of 26,875 patients from diverse populations showed that eGFR values using CKD-EPI equations had lower mean bias and performed better than the MDRD formula [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation